2013
DOI: 10.1002/gcc.22132
|View full text |Cite
|
Sign up to set email alerts
|

Novel ZC3H7B‐BCOR, MEAF6‐PHF1, and EPC1‐PHF1 fusions in ossifying fibromyxoid tumors—molecular characterization shows genetic overlap with endometrial stromal sarcoma

Abstract: PHF1 gene rearrangements have been recently described in around 50% of ossifying fibromyxoid tumors (OFMT) including benign and malignant cases, with a small subset showing EP400-PHF1 fusions. In the remaining cases no alternative gene fusions have been identified. PHF1-negative OFTs, especially if lacking S100 protein staining or peripheral ossification, are difficult to diagnose and distinguish from other soft tissue mimics. In seeking more comprehensive molecular characterization, we investigated a large co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
161
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(170 citation statements)
references
References 30 publications
7
161
2
Order By: Relevance
“…The subsequent FISH screening for potential partners identified BCOR-MAML3 fusion in an additional case, while the remaining 6 cases showed no abnormalities in MAML3 . Upon review of the literature for additional BCOR gene partners we identified ZC3H7B as a potential candidate, having been described in BCOR-ZC3H7B fusions in other sarcomas 20,25 . Thus we screened the remaining 6 BCOR -rearranged cases for ZC3H7B gene break-apart by FISH and found 2 positive cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subsequent FISH screening for potential partners identified BCOR-MAML3 fusion in an additional case, while the remaining 6 cases showed no abnormalities in MAML3 . Upon review of the literature for additional BCOR gene partners we identified ZC3H7B as a potential candidate, having been described in BCOR-ZC3H7B fusions in other sarcomas 20,25 . Thus we screened the remaining 6 BCOR -rearranged cases for ZC3H7B gene break-apart by FISH and found 2 positive cases.…”
Section: Resultsmentioning
confidence: 99%
“…17 FusionSeq is a computational method that has been successfully applied to paired-end RNA-seq data for the identification of chimeric fusion transcripts. 9,1820 Briefly, in a first step, paired end reads mapping to different genes were used to identify potential chimeric candidates. A cascade of filters, each taking into account different sources of noise in RNA-sequencing experiments, was then applied to remove spurious fusion transcripts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ING5 is a part of the ING (inhibitor of growth) family, whose founding members were initially identified as inhibitors of cell growth [122]. The EAF6 gene is rearranged in endometrial stromal sarcoma [123,124]. Thus, like MOZ and MORF, the BRPF1-ING5-EAF6 subcomplex plays a direct role in cancer.…”
Section: Brpf1 and Its Paralogs In Animal Development And Human Diseasementioning
confidence: 99%
“…The PHF1 protein acts as an accessory component of the polycomb repressive complex 2 (PRC2), which catalyzes trimethylation of histone H3 Lys27 (H3K27me3) to repress gene expression. 27 As PHF1 rearrangements are believed to be important for tumor development in other sarcomas, 28,29 it is not unlikely that loss of PHF1 function may also lead to epigenetic deregulation of PRC2 target genes.…”
Section: Discussionmentioning
confidence: 99%